2008
DOI: 10.1161/circulationaha.107.740928
|View full text |Cite
|
Sign up to set email alerts
|

Response to the Letter Regarding Article, “Evaluation of Dose-Related Effects of Aspirin on Platelet Function: Results From the Aspirin-Induced Platelet Effect (ASPECT) Study”

Abstract: appears concerned about the uniform inhibition of arachidonic acid-induced aggregation observed in the AspirinInduced Platelet Effect (ASPECT) trial. We would like to reassure Dr Klein that the compliance of the patients in ASPECT was meticulously recorded and, as reported in the manuscript, was overall 98%. Dr Klein should also be aware of the significance of results determined by double crossover studies such as the ASPECT study and the robust statistical analyses performed. 1 Why were we not surprised by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 5 publications
8
83
3
3
Order By: Relevance
“…A broad range of responses from partial to complete inhibition of aggregation was observed; we can only speculate on the influence of genetics, the current status of the organism in terms of infection, organ functions and metabolism, or external circumstances. Higher thrombocytic excitability has also been repeatedly reported in acute stroke [8,9], but its role as a consequence or underlying cause of acute stroke has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of responses from partial to complete inhibition of aggregation was observed; we can only speculate on the influence of genetics, the current status of the organism in terms of infection, organ functions and metabolism, or external circumstances. Higher thrombocytic excitability has also been repeatedly reported in acute stroke [8,9], but its role as a consequence or underlying cause of acute stroke has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported high residual platelet aggregation among patients receiving aspirin [19], particularly in patients using low doses [20]. On the other hand, lipids may increase platelet aggregation by several mechanisms [21]: (1) LDL-C, HDL-C and apolipoproteins bind specific receptors on the platelet membrane, promoting thromboxane synthesis, glycoprotein IIbIIIa expression and calcium influx [22]; (2) Modification of native LDL-C generates a platelet-activating particle [23]; and, (3) Triglycerides may also be related to platelet function.…”
Section: Antiplatelet Effects Of E10/s20 and S80mentioning
confidence: 91%
“…In a study of 120 patients with coronary artery disease taking aspirin, 9% were aspirin-resistant by TEG 8 . In the present study, 31 patients (22.1%) were aspirin resistant according to TEG.…”
Section: Discussionmentioning
confidence: 99%